Power and Ideology in Donald Trump‟s Speech at the United Nations: A Critical Discourse Analysis - Tarad Lafta, Hamid; Hassan, Hanita; Abd AI Jabbar AI Manseer, Farah; Al Mawla, Fidaa (International Journal of Psychosocial Rehabilitation, 2020)
Whenever President Trump makes a political speech, the world eagerly awaits to ascertain its political and economic implications. Economic conflicts have become an inevitable reality for all countries regarding the management of energy resources and global markets. The present research aims to analyze the political speech that Trump delivered at the United Nations (UN) Grand Hall in 2018. The purpose of this analysis is to identify how discourse related to three critical issues (i.e., the American economy, Iran, and trade with China) is used by Trump to portray a message of “us versus them.” Two approaches were employed in this study: Fairclough’s CDA (1995) and Van Dijk’s (2006) four macro-analysis strategies. The results show that Trump’s speech was, on the one hand, very comprehensive in its glorification of his administration’s achievements and, on the other hand, aggressive in its attacks on many countries for their policies that challenge the US’s position as a superpower.